The Development of Tahfiz Qur'an Movement in the Reform Era in Indonesia - Sofyan, Muhammad (Heritage of Nusantara: International Journal of Religious Literature and Heritage, 2015)
This paper is aimed to explore the development of Tahfiz Qur'an movement in the  reform era  in  Indonesia,  especially  the  developments  emerging  from  2005 until  now.  To  view  these  developments,  the  writer  will  highlight  the  Darul Qur'an institutions, ODOJ community (One Day One Juz), and methods of al-Qosimi  and  Yadain.by  using  obsrvation  and  documentery  study.  The  study found that institutions, programs and methods of Tahfiz in that era had becometransformative  Tahfizul  Qur'an,  with  modern  institutional  system,  flexible program  to  reach  almost  all  level  of  society,  innovative and  creative  learning methods  in  accordance  with  the  demand  of  today's  improvement.  However, these  developments  do  not  eliminate  the  fundamental  things  that  have  beenbuilt by the scholars of Tahfiz previously